Are family physician visits and continuity of care associated with acute care use at end-of-life? A population-based cohort study of homecare cancer patients. (February 2014) - Almaawiy, Ummukulthum; Pond, Gregory R; Sussman, Jonathan; Brazil, Kevin; Seow, Hsien
Background: Previous end-of-life cancer research has shown an association between increased family physician continuity of care and reduced use of acute care services; however, it did not focus on a homecare population or control for homecare nursing. Aim: Among end-of-life homecare cancer patients, to investigate the association of family physician continuity with location of death and hospital and emergency department visits in the last 2 weeks of life while controlling for nursing hours. Design: Retrospective population-based cohort study. Setting/participants: Cancer patients with ≥1 family physician visit in 2006 from Ontario, Canada. Family physician continuity of care was assessed using two measures: Modified Usual Provider of Care score and visits/week. Its association with location of death and hospital and emergency department visits in the last 2 weeks of life was examined using logistic regression. Results: Of 9467 patients identified, the Modified Usual Provider of Care score demonstrated a dose–response relationship with increasing continuity associated with decreased odds of hospital death and visiting the hospital and emergency department in the last 2 weeks of life. More family physician visits/week were associated with lower odds of an emergency department visit in the last 2 weeks of life and hospital death, except for patients with greater than 4 visits/week, where they had increased odds of hospitalizations and hospital deaths. Conclusions: These results demonstrate an association between increased family physician continuity of care and decreased odds of several acute care outcomes in late life, controlling for homecare nursing and other covariates.